Teacher Thinking & Professional Action - Denicolo, Pam; Kompf, Michael (Taylor & Francis, 2005)
Over the past twenty years the International Study Association on Teachers and Teaching (ISATT) has become world-renowned as an organisation dedicated to the discussion of current thinking in educational policy and practice. As such, the ideas aired at ISATT conferences are of the greatest significance to today's educational practitioners. This book satisfies the demand for a lasting record of ISATT's illuminating discussions on the theme. It is based on a selection of papers presented at their third bi-annual conference and has been updated by each contributor to include their current thoughts and opinions. Containing nineteen articles, each an in-depth examination of the topic, it is divided into four sections: conceptual frames for teacher thought and action methods and approaches to the study of teacher though and action teacher judgment and evaluation of students teacher thinking and teacher education. Broad in theme, international in scope and detailed this book is essential and enlightening reading for anyone with a serious interest in the ongoing development of educational thought.